Ethnobotany of Food Plants in The Penghulu Tribe Community in Sarolangun, Jambi - Dini Hardiani Has; Sutan Sahala Muda Marpaung; Erwika Dhora Jati; Bunga Resa Hartati; Imam Fitrianto; Iis Yulianti; Septian Putra Adi Nugroho; Yulizar Ihrami Rahmila; Fetty Dwi Rahmayanti; Ratnawaty Fadilah; Bukhari Bukhari; Asnika Putri Simanjuntak; M. Fauzhan Algiffari; Dita Anggriani Lubis (Postgraduate, University of Mataram, 2023)
Tribal community in the Bukit Bulan area, Limun District, Sarolangun Regency, Jambi. This research aims to identify the ethnobotany of food plant species by the Penghulu Tribe community in Sarolangun Regency, Jambi Province. This research was conducted in Napal Melintang and Meribung Villages. Research method ethnobotanical data on food plants were obtained through qualitative data collection techniques through in-depth interviews, in contrast, potential data were obtained through vegetation analysis and exploration methods. The study's results identified as many as 88 species from 35 families of food plants originating from cultivation and wild plants, which herbaceous plants dominated. Based on the results of interviews, there are many food plant species in the forest habitat. The part of the plant that is widely used by the community is fruit, and this is because people generally grow fruit in their yards and community gardens. Cultivators mostly use food plants for direct consumption. Conclusion this research The Penghulu tribe community's dependence on food plants is still high because they can utilize, gather, and process them. 88 species of food plants have been identified from 35 families, of which 77 produce carbohydrates, vegetables, and fruit.